Synthesis and characterization of novel polymer-hybrid silver nanoparticles and its biomedical study - Verma, Suresh Kumar; Jha, Ealisha; Kiran, K. J.; Bhat, Suresh; Suar, Mrutyunjay; Mohanty, P. S. (Materials Today: Proceedings, 2016)
Hybrid polymer metal nanoparticles have advantages over conventional metal nanoparticles with respect to their stability, chemical resistance, antibacterial activity and drug delivery properties. In the current work, we have synthesized novel stimuli-responsive polymer hybrid silver nanoparticles using green synthesis method, where the plant extract is used as a reducing agent in the synthesis. Encapsulating metal nanoparticles with stimuli-responsive soft-polymeric system is novel and provides additional versatility whose functions and properties can be tailored by controlling any of the stimuli such as pH, temperature, ionic strength with respect to their antibacterial activity and physiological condition. Moreover, green synthesis methods have advantages over conventional methods involving chemical reducing agents that are often associated with environmental toxicity because of their enhanced antibacterial and other biological effects. The synthesized hybrid particles were characterized using Dynamic light scattering, UV-Visible spectroscopy and Small angle x-ray scattering. Further, we have investigated the antibacterial and cytotoxicity effect of these hybrid particles against different bacterial cells ( Salmonella) and mammalian cell lines (HCT116) respectively. These results are discussed in the light of previous studied work and these results suggest that our synthesized polymer hybrid nanoparticles are more antibacterial and less cytotoxic than the usual silver nanoparticles. (C) 2015Elsevier Ltd.All rights reserved.
Keywords: Antibacterial effect; Cytotoxicity; Polymeric hybrid particless; silver nanoparticles

Template -free assembly in living bacterial suspension under an external electric field - Samantaray, Kunal; Bhol, Prachi; Sahoo, Bhaban; Barik, Subrat Kumar; Jathavedan, Kiran; Sahu, Bikash Ranjan; Bikash Ranjan; Suar, Mrutyunjay; Bhat, Suresh K.; Mohanty, Priti Sunda (ACS Omega, 2017)
Although template-assisted self-assembly methods are very popular in materials and biological systems, they have certain limitations such as lack of tunability and switchable functionality because of the irreversible association of cells and their matrix components. With an aim to achieve more tunability, we have made an attempt to investigate the self-assembly behavior of rod-shaped living bacteria subjected to an external alternating electric field using confocal microscopy. We demonstrate that rod-shaped living bacteria dispersed in a low salinity aqueous medium form different types of reversible freely suspended structures when subjected to an external alternating electric field. At low field strength, an oriented phase is observed where individual bacterium orients with its major axis aligned along the field direction. At intermediate field strength, bacteria align in the form of one-dimensional (1D) chains that lie along the field direction. Further, at high field strength, more bacteria associate with these 1D chains laterally to form a two-dimensional (2D) array. At higher bacterial concentration, these field-induced 2D arrays extend to form three-dimensional columnar structures. These results are discussed in the context of previously reported studies on bacterial self-assembly.
Keywords: Bacteria; Electric Properties; Self- Assembly